2022
DOI: 10.1002/bse.3040
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic capabilities for circular manufacturing supply chains—Exploring the role of Industry 4.0 and resilience

Abstract: An organisation's sustainability performance is influenced by its capabilities (skills, resources and competences) which in turn affects the performance of its entire supply chain. However, recent research has not sufficiently explored the convergence of dynamic capabilities, circular economy, resilience and Industry 4.0 concepts for manufacturing supply chains. Therefore, this study aims to identify how dynamic capabilities theory can enable circular and resilient supply chains. A qualitative research process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(62 citation statements)
references
References 102 publications
2
58
0
2
Order By: Relevance
“…Manufacturing companies strive to improve their capabilities to provide more customised products and services that meet customers' demands in a better way, on time, at a fair price, and with high quality. No doubt that Industry 4.0 is crucial for any manufacturer to understand its business and technological dimensions to implement it in a competitive and sustainable way successfully (Chari et al 2022 ; Intalar et al 2021 ; Tay et al 2021 ).…”
Section: Conclusion Implications Of the Study And Future Research Dir...mentioning
confidence: 99%
“…Manufacturing companies strive to improve their capabilities to provide more customised products and services that meet customers' demands in a better way, on time, at a fair price, and with high quality. No doubt that Industry 4.0 is crucial for any manufacturer to understand its business and technological dimensions to implement it in a competitive and sustainable way successfully (Chari et al 2022 ; Intalar et al 2021 ; Tay et al 2021 ).…”
Section: Conclusion Implications Of the Study And Future Research Dir...mentioning
confidence: 99%
“…During the last two decades, a growing concern about environmental problems has increased social and political pressure on firms to lessen their environmental impact (Galdeano‐Gómez et al, 2008). Faced with these demands, firms have gradually incorporated the management of environmental assets, practices, technologies or responsibility (environmental management systems), with the consequent increase in the strategic importance of the organisational capabilities to manage these systems (Chari et al, 2022; López‐Gamero et al, 2008; López‐Gamero et al, 2009). In this context, during recent years, research has made significant progress, clarifying the link between environmental practices and firm economic or social performance (Lee et al, 2016; López‐Gamero & Molina‐Azorín, 2016; Sharma et al, 2020).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…However, the effects obtained on environmental, and especially on social performance, are weak or non‐existent (Benitez‐Nara et al, 2021; Li et al, 2020). Finally, the literature has also found that the relationship between I4.0 technologies and sustainability is mediated by a set of dynamic capabilities linked to environmental dynamism (Bag et al, 2021; Chari et al, 2022) or by organisational change and reskilling of managers and workers (Yunus, 2021).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Frameworks (Ghisellini & Ulgiati, 2020;Iacovidou et al, 2021;Kerdlap et al, 2019;Khan & Ali, 2022;Walmsley et al, 2019), roadmaps (Vanhamäki et al, 2020), strategies (Kalmykova et al, 2018;Pan et al, 2015) and models (Chari et al, 2022).…”
Section: Circular Economymentioning
confidence: 99%